Manajemen Kewirausahaan Dalam Meningkatkan Kemampuan Edupreneurship Siswa MTs Hudatul Falah - Muhamad Fathi; Wahyu Hidayat (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to explain the role of entrepreneurship management in enhancing the edupreneurship skills of students at MTs Hudatul Falah. MTs Hudatul Falah was chosen as the research location due to its commitment to developing students' entrepreneurial abilities. This research employs a qualitative approach with data collection techniques including interviews, participatory observation, and documentation. The informants in this study include the principal, teachers, educational staff, and students who participate in entrepreneurial activities. The collected data were analyzed qualitatively using non-numerical analysis techniques, including data reduction, data display, and conclusion drawing and verification. The analysis was conducted simultaneously during and after the data collection process. The results of the study indicate that entrepreneurship management at MTs Hudatul Falah plays a significant role in enhancing the edupreneurship skills of students. This is evident from the increased competence, skills, and entrepreneurial character of students involved in entrepreneurial activities. The practical implications of this study highlight the importance of active entrepreneurship management in supporting entrepreneurial programs in schools. The findings of this research are expected to provide input for educational policymakers to strengthen the role of entrepreneurship management in efforts to improve character education in Indonesia.